Neurologic Presentation of Mitochondrial Disorders - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
Nervous system presentations in 42 children with mitochondrial disorders were analyzed by reviewing charts at the Wolfson Medical Center, Holon, and other centers in Israel.